Marine Drugs from Sponge-Microbe Association—A Review - Thomas, Tresa Remya A. (Molecular Diversity Preservation International, 2010)
The subject of this review is the biodiversity of marine sponges and associated microbes which have been reported to produce therapeutically important compounds, along with the contextual information on their geographic distribution. Class Demospongiae and the orders Halichondrida, Poecilosclerida and Dictyoceratida are the richest sources of these compounds. Among the microbial associates, members of the bacterial phylum Actinobacteria and fungal division Ascomycota have been identified to be the dominant producers of therapeutics. Though the number of bacterial associates outnumber the fungal associates, the documented potential of fungi to produce clinically active compounds is currently more important than that of bacteria. Interestingly, production of a few identical compounds by entirely different host-microbial associations has been detected in both terrestrial and marine environments. In the Demospongiae, microbial association is highly specific and so to the production of compounds. Besides, persistent production of bioactive compounds has also been encountered in highly specific host-symbiont associations. Though spatial and temporal variations are known to have a marked effect on the quality and quantity of bioactive compounds, only a few studies have covered these dimensions. The need to augment production of these compounds through tissue culture and mariculture has also been stressed. The reviewed database of these compounds is available at www.niobioinformatics.in/drug.php.